215k views
2 votes
Solve the equation r = 1/(x-1) for x in terms of r. In other words, manipulate the equation until you have x equal to an expression with r's in it but no x's.

User Shekhardtu
by
5.3k points

2 Answers

3 votes

Answer:


x=(1)/(r) +1

Explanation:


r=(1)/(x-1)

r(x-1)=1

x-1=(1)/(r)

x=(1)/(r) +1

User Sanat Gupta
by
5.1k points
2 votes

Answer:


x=(1+r)/(r)

Explanation:

Given equation:


r=(1)/((x-1))

Multiply both sides by (x - 1):


\implies r(x-1)=(1)/((x-1)) \cdot (x-1)


\implies r(x-1)=1

Expand the brackets:


\implies rx-r=1

Add r to both sides:


\implies rx-r+r=1+r


\implies rx=1+r

Divide both sides by r:


\implies (rx)/(r)=(1+r)/(r)


\implies x=(1+r)/(r)

User Rock Lee
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.